Implementation of the Living Qur'an Model in Islamic Religious Education Learning at MTsN 1 Kendari City - Maulana, Muhamad Ivan Rizki; Makinuddin, Mohammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
abstractThis study aims to describe and analyze the implementation of the Living Qur’an model in Islamic Religious Education (PAI) learning at MTsN 1 Kota Kendari. A qualitative approach with a case study design was employed. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the Living Qur’an model at MTsN 1 Kendari is implemented through daily Qur’an reading routines, Qur’an memorization programs (tahfiz), and the integration of Qur’anic values into both the learning process and school life. This model has been effective in increasing students’ interest in learning, enhancing their appreciation of Islamic values, and shaping their religious character. The findings indicate that the Living Qur’an model is not only effective in teaching Islamic Religious Education content but also plays a vital role in the contextual and practical internalization of spiritual values. This study recommends that similar models be adapted by other educational institutions as a strategy to strengthen Qur’an-based character education.Keywords: Living Qur’an, Islamic Religious Education, value internalization, MTsN 1 Kendari